EFEKTIVITAS RENDAM KAKI AIR HANGAT DENGAN SERAI TERHADAP KUALITAS TIDUR LANSIA PENDERITA HIPERTENSI DI DESA BANYU URIP, KLEGO, BOYOLALI - Widiyanto, Aris (Jurnal Informasi Kesehatan Indonesia (JIKI), 2020)
Abstract: Elderly with increasing age have a higher risk of developing hypertension. Hypertension in the elderly causes several signs and symptoms that affect daily life, one of which is the quality of sleep. The purpose of this study was to determine the effectiveness of foot soaking in warm water with lemongrass on the sleep quality of elderly people with hypertension in Banyu Urip Village, Klego, Boyolali. The research design used pre-experimental method with pre and post test approach without control. The sleep quality measurement of the elderly before and after being given a warm foot bath with lemongrass used the Sleep Quality Questioner. Sampling was taken by total sampling, a number of 36 elderly who have hypertension. The results of this study found that all elderly with hypertension as many as 36 respondents experienced poor sleep quality and after the intervention the majority of elderly with hypertension experienced good sleep quality as many as 32 respondents. The Wilcoxon test found that soaking feet in warm water with lemongrass was effective in improving the sleep quality of elderly people with hypertension in Banyu Urip Village, Klego, Boyolali with a p value of 0.000 (p <0.05). It is hoped that the elderly can improve the quality of their sleep by utilizing lemongrass which is used as a regular warm water foot soak mixture.